Improving 2nd Graders’ Calculation Skill through Pathilan Traditional Game - Anisatul Farida (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2016)
This research was carried out by the fact that many students are not interested in mathematics, and their calculation skill is still under expectation. Less of student engagement and too much teacher intervention are still dominating along mathematics learning process. This study aimed to improve 2nd grade students’ calculation skill through Pathilan traditional game in MI Muhammadiyah Bekangan. This research subject were 29 2nd graders of MI Muhammadiyah Bekangan period 2015/2016. This research combines classroom action research which refers to Stephen Kemmis and Robin Mc Taggart. This research was conducted in two cycles and each cycle was done in two meetings. Every cycle consisted of 4 steps i.e. preparation, action, observation, evaluation, analysis and reflection. The technique of collecting data was done by assessing test result and observation, test instrument, observation sheet, and field notes. The data was analyzed by using quantitative-descriptive approach. The study showed that students’ learning results were bellow minimum limit of 50% completeness before the implementation Pathilan traditional game during learning process. After the implementation of Pathilan traditional game, the percentage of students’ learning results that passed minimum limit (KKM) of 50% completeness was improving, from 75,86% in the first cycle to 86,21% in the second cylce. The average of students’ learning result was also improving from 67,83 becomed 75,79 in the last cycle. In the end, learning with Pathilan traditional game could motivate students to study calculation continuously